Sustainable Rail Transport Proceedings of RailNewcastle 2017 - Fraszczyk, Anna; Marinov, Marin (Lecture Notes in Mobility, 2019)
These conference proceedings include a collection of articles presented at the RailExchange conference in October 2017 at Newcastle University, UK. They will be useful for researchers in developing countries looking for opportunities of knowledge exchange. The RailExchange project aimed to develop sustainable railway education in Thailand, via international partnerships and industry collaborations based around stakeholders' expertise and experiences. It involved staff exchange (academics and researchers) between Mahidol and Newcastle University for joint research and curriculum development and also organizing railway conferences and workshops in both Thailand and the UK. The papers published here focus on rail-related issues and present a perspective of a widely understood 'exchange' in academia and industry environments. 'Exchange' is perceived as rail knowledge exchange between partners, rail staff exchange between academia and/or industry, research exchange between teams, student-lecturer knowledge exchange, academia-industry collaboration, etc. In addition, more general rail-related papers are also included.